Attitude of Inpatients about Information Technologies - F Sadooqi; M Ahmadi; M.R Gohari; F Rangraz Jeddi (Tehran University of Medical Sciences, 2010)
Background and Aim: Information Technologies (ITs) has become a significant resource for dissemination of information and resulted to an increase of health knowledge in communities. With attention to patient - centered approach this study was done to determine knowledge of inpatients about ITs. Materials and Methods: A descriptive - cross-sectional study was done on 461 inpatient in Kashan University of Medical Sciences hospital's with a reliable (spearman Brown, r =0.83) and valid (face and content) questionnaire in two section, demographic information and study objects. Data gathering was done with interview then analyzed by SPSS and descriptive analysis. Results: %42.1 and %26.7 of participants had knowledge about computer and the Internet relatively. %41.9 of them had the Internet access. 86.3% and 88.3% relatively would be interested to access and get medical records and their information. They intended to get test (%85.7), refill her/his prescription (79%), get appointment (%76.4), consult with physicians (%80), and get information about diets (80%) through ITs. Discussion  and Conclusion: It seems ITs attitude in inpatients is relatively good. Providing their information needs especially about prescription order and diets from CD or the Internet by hospital sites and introducing good medical sites to patient were recommended.